Treatment outcomes, medication adherence and predictors among patients with epilepsy in Mekelle City Hospitals, Ethiopia: a multicentre observational cross-sectional study - Kidu Gidey; Alemseged Beyene Berha; Gebremicheal Gebreyohanns Kahsay (BMJ Open)
Objective This study aimed to assess treatment outcome, medication adherence and predictors among epilepsy patients at three low-resource setting hospitals in Mekelle City, Northern Ethiopia.Design A multicentre hospital-based observational cross-sectional study was conducted.Setting The study was conducted in three resource-limited tertiary care hospitals in Mekelle City, Northern Ethiopia: Ayder Comprehensive Specialized Hospital, Mekelle General Hospital and Quiha General Hospital.Participants A total of 351 patients with epilepsy receiving regular follow-up care at adult neurology outpatient clinics in three low-resource setting hospitals were included in the study.Main outcome measures The study assessed adherence to antiepileptic drugs (AEDs), treatment outcomes and identified independent predictors of these outcomes.Results A total of 351 study participants were included in the final analysis, with a mean (±SD) age of 37.98±14.27 years. More than one-third (39%) had poorly controlled seizures. Living in urban areas (adjusted odds ratio (AOR)= 3.36, 95% CI 1.1 to 10.4, p=0.037), being government-employed (AOR = 4.0, 95% CI 1.1 to 14.5, p=0.035) and being a student (AOR = 4.0, 95% CI 1.1 to 14.5, p=0.035) were associated with good seizure control. Half of the participants (177, 50.6 %) were non-adherent to their medications. Being a farmer (AOR = 4.2, 95% CI 1.5 to 11.3, p=0.005), a housewife (AOR = 4.9, 95% CI 1.4 to 17.2, p=0.012), absence of seizure-triggering factors (AOR = 3.7, 95% CI 2.34 to 6.06, p<0.001), absence of comorbidities (AOR 1.8, 95% CI 1.11 to 11.28, p=0.008) and good seizure control (AOR= 2.38, 95% CI 1.55 to 3.71, p<0.001) were predictors of adherence to AED treatment.Conclusions More than two-thirds of patients with epilepsy experienced poor seizure control. Place of residence, employment status and the number of seizure episodes prior to treatment initiation were identified as significant predictors of treatment outcomes. Approximately half of the study participants were adherent to their medications, with employment status, the presence of seizure-triggering factors, comorbidities and seizure control serving as predictors of medication adherence.